Thinking after Drinking: Impaired Hippocampal-Dependent Cognition in Human Alcoholics and Animal Models of Alcohol Dependence - Staples, Miranda C.; Mandyam, Chitra D. (Frontiers in Psychiatry, 2016)
Alcohol use disorder currently affects approximately 18 million Americans, with at least half of these individuals having significant cognitive impairments subsequent to their chronic alcohol use. This is most widely apparent as frontal cortex dependent cognitive dysfunction, where executive function and decision making are severely compromised, as well as hippocampus dependent cognitive dysfunction, where contextual and temporal reasoning are negatively impacted. This review discusses the relevant clinical literature to support the theory that cognitive recovery in tasks dependent on the prefrontal cortex and hippocampus is temporally different across extended periods of abstinence from alcohol. Additional studies from preclinical models are discussed to support clinical findings. Finally, the unique cellular composition of the hippocampus and cognitive impairment dependent on the hippocampus is highlighted in the context of alcohol dependence.